The paradise notebooks : 90 miles across the Sierra Nevada - Nevle, Richard J.; Nightingale, Steven (Comstock Publishing Associates, Cornell University Press, 2022)
"Considers twenty-one elements of the Sierra Nevada-from granite to aspen to a species of butterfly-in pairs of essays. The first looks at the natural history and science of each element; the second treats the element through poetry and the lens of mysticism. Interwoven are vignettes from a 2017 backpacking trip"--Provided by publisher.